MEDICAL AND SOCIAL ISSUES OF MORTALITY AMONG ORPHANS - S.R. Konova ("Paediatrician" Publishers LLC, 2007)
The article is dedicated to the issues of the level and structure of morbidity, invalidity of the orphans. The author has analyzed the reasons for the orphans' deaths in detail. She estimated the level and quality if the medical care for the orphans. There are some organization approaches to solve the existing issues of complex medical and social care for the children of this category.Key words: children, orphanage, morbidity, invalidity, mortality.